(untitled) (Journal of Economic Research & Business Administration, 2016)
In the article, not considered deolog esk e and moralno t esk e aspects kategor eskogo zapreta on application of sswdnogo per cent in economic sdelkax. Anal z rwyutsya causes, podtverjdayu e skr twyu Usage opasnost procentn x Relations in Traditional financial operations, pr vodyatsya mnen ya scientists and relatively celesoobraznost otkaza from sswdnogo per cent, ssledovan also opened vayutsya prospects of the development of Islamic Banks in Kazakhstan.